1993
DOI: 10.1096/fasebj.7.10.8344492
|View full text |Cite
|
Sign up to set email alerts
|

Dosage‐dependent dominance over wild‐type p53 of a mutant p53 isolated from nasopharyngeal carcinoma 1

Abstract: Mutational inactivation of p53, a tumor suppressor gene, is the most common genetic alteration found in human cancer. Most mutated p53s either lose tumor suppressor function or gain oncogenic activity. We recently reported the detection of a heterozygous point mutation of p53 at codon 280 in nasopharyngeal carcinoma (NPC) (1), a high-incidence malignancy in southern China and southeast Asia. Given its heterozygous state, in which both wild-type and mutated p53 gene were expressed, p53-thr280 should function do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
40
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 1 publication
1
40
0
Order By: Relevance
“…The wildtype p53 containing U2-OS cells were transiently transfected with the reporter and subjected to etoposide treatment. As shown in Figure 3d, etoposide increased luciferase activity steadily in an incubation timedependent manner reaching a twofold peak at 24 h. To further confirm that the etoposide-induced transactivation is p53-dependent, we transfected p53-280T, a known dominant-negative p53 mutant (Sun et al, 1993a;Wallingford et al, 1997), into U2-OS cells, followed by etoposide treatment and luciferase assay. As a control, the empty vector was used.…”
Section: Rps27l Induction By P53 H He and Y Sunmentioning
confidence: 77%
See 1 more Smart Citation
“…The wildtype p53 containing U2-OS cells were transiently transfected with the reporter and subjected to etoposide treatment. As shown in Figure 3d, etoposide increased luciferase activity steadily in an incubation timedependent manner reaching a twofold peak at 24 h. To further confirm that the etoposide-induced transactivation is p53-dependent, we transfected p53-280T, a known dominant-negative p53 mutant (Sun et al, 1993a;Wallingford et al, 1997), into U2-OS cells, followed by etoposide treatment and luciferase assay. As a control, the empty vector was used.…”
Section: Rps27l Induction By P53 H He and Y Sunmentioning
confidence: 77%
“…Plasmid DNAs expressing p53 mutants were individually co-transfected into p53-null H1299 cells with S27L-w/p53 luciferase reporter. The p53 mutants used were the p53-143A, p53-175H, p53-248W, p53-273H, four p53 mutants most commonly found in human cancers (Hollstein et al, 1991) and p53-280T, a dominant negative p53 mutant found in nasopharyngeal carcinomas (Sun et al, 1993a;Wallingford et al, 1997). As shown in Figure 3c, in contrast to wild-type p53, all the p53 mutants failed to induce any significant transactivation of the luciferase reporter.…”
Section: Rps27l Induction By P53 H He and Y Sunmentioning
confidence: 99%
“…Several luciferase reporter plasmids driven by a p53 speci®c binding site derived from the mouse Mdm-2 gene, Waf-1 gene, or synthetic p53 binding site (PG13) (Juven et al, 1993;El-Deiry et al, 1993;Kern et al, 1991) were used for transfection. The recipient cells include L-RT101, a mouse JB6 tumor line, and HTx, a spontaneously transformed mouse liver line, both harboring endogenous wildtype p53 (Sun et al, 1993b,c), and human Saos-2 cells, lacking endogenous p53 (cotransfected with wildtype p53 in this case) (Sun et al, 1993a). Transient transfectants were then exposed to reductants (DTT, 1 mM; glutathione, GSH, 5 mM; or N-acetyl-L-cysteine, 5 mM) or oxidants (H 2 O 2 , 0.1 mM; paraquat, 0.5 mM; oxidized DTT, 2.5 mM; GSSG, 5 mM; or diamide 0.2 mM), to metals (zinc sulfate, 10 mM; cuprous chloride, 20 mM; p-chloromercurphenylsulfonic acid, 8 mM; or mercury chloride, 3 mM), or metal chelators (OP, 150 mM, dipicolinic acid, 150 mM; or diethylenetriamine-acetic acid, 50 mM), to compounds which inhibit endogenous GSH synthesis (L-buthionine sulfoximine, 10 mM), or simply to antioxidants (butylated hydroxy-anisole, 10 mM, or pyrrolidine dithiocarbamate 300 mM).…”
Section: Resultsmentioning
confidence: 99%
“…The Rb DNA sequence in each cell line shows no rearrangement or deletion, but Rb mRNA and protein expression are variable from cell to cell in each cell line. Because mutation of the p53 gene has been found in many other tumor cells (Caron de Fromentel and Soussi 1992;Hollstein et al 1991;Levine et al 1991;Rotter and Prokocimer 1991;Eliyahu et al 1989;Finlay et al 1989) and in a few NPC cases (Sun et al 1992(Sun et al ,1993Effert et al 1992;Spruck et al 1992), we wanted to know whether our cell lines also contained a mutated p53 gene.…”
mentioning
confidence: 99%